The Optimal Scaling Combination of Age and Body Mass Index as an Index of Metabolic Syndrome for Postmenopausal Taiwanese Women. (March 2015) - Ho, Cheng; Chang, Chia-Hao; Yen, Ching-Ho
The aim of this study was to combine as a new index age with an anthropometric indicator of obesity that is more closely associated with metabolic syndrome (MS) risk than other anthropometric indicators for postmenopausal Taiwanese women. In this cross-sectional study, data were collected from 1128 postmenopausal women volunteers during the period from September 2008 to December 2009. Receiver operating characteristic (ROC) curves for assessing the risk of MS for postmenopausal Taiwanese women were computed for the optimal scaling combination (OSC) and anthropometric indicator of obesity. The area under the ROC curves of the OSC was significantly larger than those of the anthropometric indicator. OSC ≥ 4.98 was found to be the most prevalent cutoff point. The present investigation suggests that the OSC could be used in clinical practice as a simple parameter for the identification of postmenopausal Taiwanese women at risk of MS.